A review of thin-film transistors/circuits fabrication with 3D self-aligned imprint lithography. (13th March 2017) - Li, Shunpu; Chu, Daping
Abstract: Nanoimprint lithography (NIL) is a promising method for the fabrication of micro/nanostructures through a simple, low-cost, and high throughput process. Imprinted 2D structure with high resolution has been demonstrated successfully for certain applications including magnetic hard disks and optical gratings. Manufacturing low-cost electronic devices that require patterned multi-layers with NIL is very challenging, particularly for those requiring different patterns. In recent years, considerable effort has been made using the self-aligned imprinting technique, opening an alternative way to develop and fabricate complementary flexible electronics. In this paper we review thin film transistor (TFT) fabrication with 3D self-aligned imprint lithography (SAIL), which enables the patterning and alignment of submicron features on meter-scale flexible substrates in the roll-to-roll configuration. The 3D SAIL solves the problem of precision interlayer registry of devices on a moving web by encoding all geometric information required for all device patterning steps into a monolithic imprinted 3D structure.